Validity Triage and Response Time Nurses in hospitals emergency room Sheikh Yusuf Gowa - Annisa, Thahirah; Wahdaniah; Risnah; Ridwan, Saleh (Journal Of Nursing Practice, 2020)
Background: triage is a complex decision-making process in order to determine which patients are at risk of death, disabilities, poor clinical situation deteriorates, and safe patient for waiting. One of the principles of response time is generally about handling emergency patients who should be treated later than five (5) minutes after arriving at the Emergency Room.Purpose: The objective is to know the relationship between the Response Time Validity triage the nurse.Methods: The study design was observational analytic with cross sectional approach to sampling using Accidental Sampling based on inclusion and exclusion criteria with the number of 18 respondents. Univariate test results obtained from 11 respondents do Triage with appropriate and quick response time doing about 8 respondent. To determine the relationship between the validity of triage and response time by using Spearman rank test test at the significance level of 95%, which gained significant value of p = 0.000 or less than 0.05 (0.000 <0.05).Results: The results of this study to indicate there is a relationship between the validity Triage and Response Time Hospital emergency room nurse in Sheikh Yusuf Gowa Hospital. Conclusion: It is expected that this study can be used as a reference for educational institutions and health care institutions.